The Bid Challenge Procedures under the WTO Government Procurement Agreement: A Critical Study of the Hong Kong Experience - GAO, Henry (Institutional Knowledge at Singapore Management University, 2007)
While there has been an extensive literature on the challenge procedure of the WTO Government Procurement Agreement (GPA) in general, as well as excellent country studies on the operation of the national challenge procedures of several key GPA Members, no such study has been conducted for Hong Kong yet. In the view of the author, even though Hong Kong has a relatively small procurement market, it combines the features of a clean and effective government and a highly internationalised procurement market, and thus makes an interesting subject of study. In this article, the author examines the efforts made by the Hong Kong Government to implement its obligation under the GPA to provide challenge procedures. The article starts by reviewing Hong Kong's participation in the government procurement agreements under the GATT and WTO, and then sets out the general background to the Review Body for Bid Challenges of Hong Kong. In the next section, the article discusses in detail the bid challenge procedures and how such procedural rules have been applied and elaborated through the cases that came before the Review Body. The article concludes by noting that the bid challenge system in Hong Kong generally conforms to its GPA obligations.